2022
DOI: 10.3390/ijms23136969
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Structural and Dynamical Flexibility of Myelin Basic Protein in Response to Guanidinium Chloride

Abstract: Myelin basic protein (MBP) is intrinsically disordered in solution and is considered as a conformationally flexible biomacromolecule. Here, we present a study on perturbation of MBP structure and dynamics by the denaturant guanidinium chloride (GndCl) using small-angle scattering and neutron spin–echo spectroscopy (NSE). A concentration of 0.2 M GndCl causes charge screening in MBP resulting in a compact, but still disordered protein conformation, while GndCl concentrations above 1 M lead to structural expansi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Previous NSE studies on the dynamics of SCNPs in dilute solutions revealed the relaxation of internal degrees of freedom, but clearly slowed down with respect to their linear precursor counterparts. , This effect is attributed to the internal friction associated with the compartmentalization in domains within the macromolecule. To describe the dynamic structure factor, the dual polymer/NP character of the SCNPs in solution was considered by applying theoretical approximations based on the Zimm model. , Similar dynamic behavior has been found from NSE investigations on solutions of IDPs and protein chains unfolded by denaturing, with a relatively large contribution of internal dynamics to the overall diffusion but a slowing down of the more local modes. This effect can be taken into account by adding an internal friction and is essentially the same effect found in SCNPs.…”
Section: Introductionmentioning
confidence: 81%
“…Previous NSE studies on the dynamics of SCNPs in dilute solutions revealed the relaxation of internal degrees of freedom, but clearly slowed down with respect to their linear precursor counterparts. , This effect is attributed to the internal friction associated with the compartmentalization in domains within the macromolecule. To describe the dynamic structure factor, the dual polymer/NP character of the SCNPs in solution was considered by applying theoretical approximations based on the Zimm model. , Similar dynamic behavior has been found from NSE investigations on solutions of IDPs and protein chains unfolded by denaturing, with a relatively large contribution of internal dynamics to the overall diffusion but a slowing down of the more local modes. This effect can be taken into account by adding an internal friction and is essentially the same effect found in SCNPs.…”
Section: Introductionmentioning
confidence: 81%
“…They also found the same densification behavior of MBP. The difference was that at high concentrations of GndCl, MBP exhibited repulsive intra-chain interactions, with structure swelled and relaxation time increased [61]. The emerging field of intrinsically disordered proteins expands our understanding of protein structure-function relationships and emphasizes the importance of protein flexibility and conformational variability in cellular processes.…”
Section: Proteinsmentioning
confidence: 99%